ANALISIS KEMAMPUAN GURU DALAM MEMBUAT SOAL TIPE HOTS (HIGH ORDER THINKING SKILLS)MATA PELAJARAN MATEMATIKA - Pratiwi, Lely Fitriyanti (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this study was to describe the teacher's ability to make HOTS (High Order Thinking SKills) type questions for mathematics lessons. This research uses descriptive qualitative method. . Data collection with documentation and interview techniques. The data were analyzed by comparing Bloom's Taxonomy and the criteria for HOTS questions, starting with the data reduction stage, presenting the data and ending with drawing conclusions. Test the validity of the data using source triagulation. The results showed that the percentage of HOTS questions did not meet the criteria of 12% and 60% of LOST questions. In addition, the obstacles faced by teachers are limited time, not understanding in finding and matching KKO (Kata Kerja Operational), sometimes inappropriate selection of KD (Kompetensi Dasar), lack of socialization, still making questions with the same model.